Bathymetry mapping using VNREDSAT-1 image: A case study in Ninh Hai coast, Ninh Thuan province of Vietnam - Khin, La Van; Son, Tong Phuoc Hoang; Huan, Nguyen Huu; Trung, Pham Ba (Vietnam Journal of Marine Science and Technology, 2019)
Bathymetry mapping of coastal zones is one of the minimum requirements to serve related activities as marine management, transportation, construction and scientific application. However, the traditional method of direct measurement in the fields meets problems of time consuming, manpower and money. Applying remote sensing techniques to establish bathymetry in shallow water is an effective method to overcome the traditional problems. The objective of this study is to use VNREDSAT-1 data to map the bathymetry in a coastal region of Vietnam and Ninh Hai coast was selected as a case study in this research. The image was acquired on September 4th, 2013 and preprocessed through atmospheric correction using 6S model and sun glint removal by Hedley method. A total of 3,642 collected data points were divided into two parts, the first part of 2,810 points used to build up the model and the rest of 832 points for validation. The model used is based on multiple regression methods with four independent variables as four bands and a dependent variable as water depth. The results show that the models got high accuracy at the water depth from 10 m to 19 m with root mean square error of 1.03 m to 1.99 m and correlation coefficients of 0.72 to 0.74. This study demonstrates the capacity of VNREDSAT-1 in bathymetry mapping, and it would be an efficient tool for precisely mapping crude bathymetry in Vietnam